Milk fat globule EGF factor 8 restores mitochondrial function via integrin‐medicated activation of the FAK‐STAT3 signaling pathway in acute pancreatitis - Yifan Ren; Wuming Liu; Lin zhang; Jia Zhang; Jianbin Bi; Tao Wang; Mengzhou Wang; Zhaoqing Du; Yawen Wang; Lin zhang; Zheng Wu; Yi Lv; et al. (Clinical and Translational Medicine, 2021)
Abstract Acute pancreatitis (AP) remains a significant clinical challenge. Mitochondrial dysfunction contributes significantly to the pathogenesis of AP. Milk fat globule EGF factor 8 (MFG‐E8) is an opsonizing protein, which has many biological functions via binding to αvβ3/5 integrins. Ligand‐dependent integrin‐FAK activation of STAT3 was reported to be of great importance for maintaining a normal mitochondrial function. However, MFG‐E8's role in AP has not been evaluated. Methods Blood samples were acquired from 69 healthy controls and 134 AP patients. Serum MFG‐E8 levels were measured by ELISA. The relationship between serum concentrations of MFG‐E8 and disease severity were analyzed. The role of MFG‐E8 was evaluated in experimental models of AP. Results Serum concentrations of MFG‐E8 were lower in AP patients than healthy controls. And serum MFG‐E8 concentrations were negatively correlated with disease severity in AP patients. In mice, MFG‐E8 administration decreased L‐arginine‐induced pancreatic injury and mortality. MFG‐E8's protective effects in experimental AP were associated with improvement in mitochondrial function and reduction in oxidative stress. MFG‐E8 knockout mice suffered more severe pancreatic injury and greater mitochondrial damage after l‐arginine administration. Mechanistically, MFG‐E8 activated the FAK‐STAT3 pathway in AP mice. Cilengitide, a specific αvβ3/5 integrin inhibitor, abolished MFG‐E8's beneficial effects in AP. PF00562271, a specific FAK inhibitor, blocked MFG‐E8‐induced STAT3 phosphorylation. APTSTAT3‐9R, a specific STAT3 antagonist, also eliminated MFG‐E8's beneficial effects under such a condition. Conclusions MFG‐E8 acts as an endogenous protective mediator in the pathogenesis of AP. MFG‐E8 administration protects against AP possibly by restoring mitochondrial function via activation of the integrin‐FAK‐STAT3 signaling pathway. Targeting the action of MFG‐E8 may present a potential therapeutic option for AP.